An evaluation of online flipped instruction methods during the COVID-19 pandemic. Issue 1 (2nd January 2021) - Sanandaji, Anahita; Ghanbartehrani, Saeed
ABSTRACT: The COVID-19 pandemic caused a sudden switch from face-to-face to online instruction. Switching from face-to-face instruction into fully online classes in a short timeframe could be challenging especially for instructors with little or no online teaching experience. In this research, we design, implement, and evaluate a novel framework to transform face-to-face classes into online flipped instruction for Information Systems (IS) courses. Our proposed framework uniquely combines backward design approach with flipped classroom methodology customized for online education. The framework was successfully applied to the IS courses offered in two colleges in a public university in the US during the COVID-19 period. We measured the effectiveness of the online flipped course elements based on the students' feedback and developed design considerations and teaching tips to be used during and after the COVID-19 era.